The International Competition For Gas: The War On Pipelines And Supplies - صيوح لؤي; عبود ذوالفقار; أبو حسين لؤي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
With the increasing importance of natural gas globally, a conflict of another kind has emerged to control this strategic commodity, by controlling the passage of gas pipelines that cross countries, continents and seas, which are getting longer day after day, as tens of kilometers of them are added daily on the surface of the planet. Serves as the arteries of the heart for many countries, especially Western European countries. Also, the global demand for this substance is still doubling every ten years as a result of the increasing needs. Since the beginning of this century, a number of plans have been drawn up to extend gas pipelines, some of which have already started, and some are still under planning. Russia has been the first to implement some of these lines to strengthen Its position in the European energy market in the long run, and the Europeans and Americans have also drawn up strategic plans to extend gas pipelines as a strategic option to limit Russia’s dominance in the European and global energy market, considering energy from oil and gas nerve and the economic engine for the renaissance of economic countries, and an element of strength for countries of origin and countries Corridor and downstream countries